2015
DOI: 10.1111/1365-2435.12408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trap colour and trap‐flower distance on prey and pollinator capture in carnivorous Drosera species

Abstract: Summary1. The functional features of carnivorous plants' traps have been mostly interpreted as adaptations to capture prey. Carnivorous plants that feed on insects, however, run the risk that increasing trapping effectiveness might in turn reduce reproductive success through capture of pollinators. Such a pollinator-prey conflict might play an important role in the evolution of trap features. In carnivorous plants with sticky leaves (e.g. Drosera, Pinguicula), both spatial distance between traps and flowers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
1
17
0
3
Order By: Relevance
“…In Drosera species, some of which also bear flowers on tall scapes, absolute height aboveground (and thus visibility to pollinators)-rather than flower-trap separation-appears to be the trait under selection, even though separation may sometimes reduce pollinator bycatch (Anderson and Midgley 2001;Anderson 2010;El-Sayed et al 2016). Red Drosera trap color, on the other hand, deters pollinators but does not attract prey; Jürgens et al (2015) suggest that selection against pollinator-prey overlap may favor this trait. The results we present for D. muscipula build a foundation for its inclusion in evolutionary ecological studies of the carnivore's dilemma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Drosera species, some of which also bear flowers on tall scapes, absolute height aboveground (and thus visibility to pollinators)-rather than flower-trap separation-appears to be the trait under selection, even though separation may sometimes reduce pollinator bycatch (Anderson and Midgley 2001;Anderson 2010;El-Sayed et al 2016). Red Drosera trap color, on the other hand, deters pollinators but does not attract prey; Jürgens et al (2015) suggest that selection against pollinator-prey overlap may favor this trait. The results we present for D. muscipula build a foundation for its inclusion in evolutionary ecological studies of the carnivore's dilemma.…”
Section: Discussionmentioning
confidence: 98%
“…They may therefore face trade-offs between pollination services and nutrient intake, known as pollinator-prey conflict (Juniper et al 1989;Zamora 1999;Jürgens et al 2012). For example, recent experiments suggest that the red color of sundew (Drosera) traps reduces pollinator bycatch but at the expense of total prey capture (Jürgens et al 2015). With few exceptions, however, the extent and strength of pollinator-prey conflict is poorly quantified (but see Zamora 1999;Murza et al 2006;El-Sayed et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a conspicuous feature of Nepenthes, pitcher coloration is poorly understood. A few studies have examined the role of red pigmentation as a visual signal in carnivorous plants (Schaefer & Ruxton, 2008;Bennett & Ellison, 2009;Foot, Rice, & Millet, 2014;Jürgens et al, 2015;El-Sayed, Byers, & Suckling, 2016), and a number have hypothesized that the contrast of red against a green background of foliage could be attractive, although many insects lack red perception (Briscoe and Chittka, 2001). Red was not found to be a prey attractant in studies with sundews (Foot, Rice, & Millet, 2014;Jürgens et al, 2015;El-Sayed, Byers, & Suckling, 2016), but results have been conflicting in pitcher plants (Schaefer & Ruxton, 2008;Bennett & Ellison, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are prominent in the vegetative tissues of several evolutionarily distinct carnivorous plant families, and an emerging argument suggests that these pigments serve a role in prey capture (Joel 1988, Jürgens et al 2015, Moran et al 1999. Schaefer and Ruxton (2008) demonstrated that the markedly red coloration on the pitchers of Nepenthes (tropical pitcher plants) species may enhance prey capture compared to pitchers without red coloration.…”
Section: Introductionmentioning
confidence: 99%
“…(Spoon-leaved Sundew) are produced when the plants become nitrogen deficient, and that this pigment production subsequently increases prey attraction in both species, providing a means to regain nutrients lacking in the substrate. Jürgens et al (2015) proposed that anthocyanins reduce the risk of pollinator-prey conflict in sundew species because the pigments tended to deter pollinating insects while still attracting insect prey, but the red-pigmented leaves also lowered total prey-capture. The debate associated with the involvement of red pigmentation in prey capture is due partly to the widely accepted argument that insects' color vision is poor in the red spectrum of light (Bennett andEllison 2009, Chittka et al 2001).…”
Section: Introductionmentioning
confidence: 99%